2019
DOI: 10.1111/andr.12602
|View full text |Cite
|
Sign up to set email alerts
|

Genitourinary cancer patients have worse baseline semen parameters than healthy sperm bankers

Abstract: Background: While the spermatotoxic properties of cancer treatments such as chemotherapy and radiation therapy are widely recognized, the effect of malignancy itself on male fertility is not clearly understood. Objectives: To determine whether malignancy is associated with diminished semen quality prior to spermatotoxic treatment among sperm bankers. Materials and Methods: Retrospective database review of de-identified records was obtained for all episodes of sperm banking performed at a cryobank from January … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 20 publications
1
12
0
Order By: Relevance
“…To date, there are still controversies regarding the effects of malignant neoplasm itself on semen quality before clinical treatments. Consistent with most previous studies, we found that malignant neoplasm patients had significantly lower semen quality before specific antineoplastic treatments 5,12 . However, some studies did not observe reduced semen quality in malignant neoplasm patients before chemotherapy or radiation treatments.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…To date, there are still controversies regarding the effects of malignant neoplasm itself on semen quality before clinical treatments. Consistent with most previous studies, we found that malignant neoplasm patients had significantly lower semen quality before specific antineoplastic treatments 5,12 . However, some studies did not observe reduced semen quality in malignant neoplasm patients before chemotherapy or radiation treatments.…”
Section: Discussionsupporting
confidence: 91%
“…The results of previous studies investigating the effects of malignant neoplasms on semen quality were somewhat inconsistent. Some studies found reductions in semen quality in malignant neoplasm patients including lower sperm count, motility, and/or normal forms, 4,5 while other studies did not observe any association between malignant neoplasms and semen quality 6–9 . The inconsistency may result from the lack of a comparable control group, which is critical in adequately assessing the effect of malignant neoplasms on semen quality.…”
Section: Introductionmentioning
confidence: 99%
“…Chemotherapy, radiotherapy, and radical surgical procedures might irreversibly impair spermatogenesis and/or ejaculation. Cancer itself can also affect fertility directly (eg, testicular cancer and Hodgkin's lymphoma) 8 . Currently, the only reliable method of fertility preservation in reproductive‐aged men with cancer is sperm banking 9 .…”
Section: The Impact Of Sars‐cov‐2 For Males In Need Of Sperm Bankingmentioning
confidence: 99%
“…Cancer itself can also affect fertility directly (eg, testicular cancer and Hodgkin's lymphoma). 8 Currently, the only reliable method of fertility preservation in reproductive-aged men with cancer is sperm banking. 9 Sperm banking must be ideally completed before the start of gonadotoxic therapy.…”
Section: Cancer Patientsmentioning
confidence: 99%
“…Two studies in this issue looked closely at the semen parameters in patients with TGCT. A large clinical study from a semen bank confirmed that TGCT patients had decreased sperm concentration and total motile sperm count even before treatment (Xu et al , ). Similar findings are reported in another translational study, which followed these observations by comparing the proteomic profiles of spermatozoa from testicular cancer patients with asthenozoospermia and normospermia, and found quantitative changes in several proteins involved in mitochondrial function, oxidative phosphorylation and fertilisation (Panner Selvam et al , ).…”
mentioning
confidence: 91%